Study on the optimization of the decolorization of orange essential oil - Ren, Jing-Nan (Food Sci Biotechnol, 2018)
The effects of diatomite, activated clay and acticarbon on the decolorization of orange essential oil were investigated. Single factor and orthogonal tests were performed to determine the optimum discoloring conditions. The results showed that the activated clay exhibited the most satisfactory effect on discoloring. Then it was used as the decolorizer for the decolorization of orange essential oil. The highest decolorization rate (84.5%) was obtained using 10% activated clay at 60 °C for 30 min. The contents of oxygenated compounds (linalool and citral) increased from 1.4 to 3.1% after decolorization. Sensory assessment revealed that the orange essential oil after decolorization using activated clay had a mellow and characteristic orange aroma. Chromaticity analysis showed that it had excellent transparency and yellow color under the optimized condition. Thus, decolorization with activated clay could maintain the quality and prolong the storage of orange essential oil.